Pengaruh Kematangan Buah dan Pengupasan Sabut Terhadap Kecepatan Kecambah, Daya Kecambah dan Vigor Bibit Pinang - MIFTAHORRACHMAN, MIFTAHORRACHMAN; IQBAL, TEUKU A. (Buletin Palma, 2009)
Effect of Fruit Maturity and Unhusked Treatment to Rate of Germination, Viability and Vigor of Arecanut SeedlingEffect of seed maturity and seed peeling to viability, germination rate and vigor of arecanut seedlings was assessed in May to July 2008 using arecanut ex situ collection of Kayuwatu Experimental Garden. Research was conducted in factorial experiment 3 x 2 x 4 by using randomized block design. Each treatment consists of four replications and each replication consists of 15 seeds. The results showed that seed maturity and seed peeling gives siqnificant effect on germination rate, viability, and seedlings vigor. Nine-month-old seeds without husks has the fastest germination rate (24.73 days) than other combination treatments. Eleven month old seeds without husks has the highest viability (90.00%). Twelve month old seeds either whole nut or without husk gave the highest seedling vigor.